Prevalence of Aspergillus sp. contamination in commercial poultry feed and feed ingredients in Malaysia - Roslan, Zahidah (2016)
Mycotoxins can occur naturally in feedstuffs and may endanger the health of livestock and man. They develop as toxic metabolites when temperature and humidity are optimum for the growth of certain fungi on feedstuff, whether in the field, in transport or in storage, or during processing and manufacturing. This study was conducted to determine the occurrence of Aspergillus sp. (AS) contamination in poultry feed. Feed samples were bought from several petshops in Bangi, Kajang, and Serdang areas. The four brands of commercial broiler diet consisted of broiler starter and grower- finisher diets. The fungal counts for all commercial brands and all feed ingredients were conducted and results were compared between each feedstuff. The fungal species were isolated from the all feed samples cultured on sabouraud dextrose agar. They were identified macroscopically and microscopically after being incubated under room temperature for a week. The results showed that AS isolated from feed ingredients was highest in grade A corn (1.9 x 10² cfu/g) and soybean meal (0.7 x 10² cfu/g). Among commercial diets, Brand A had the highest fungal count (2.1 x 10² cfu/g) and Brand D had zero fungal count for broiler starter diet. For grower-finisher complete feed, Brand D had the highest fungal count (3.1 x 10²cfu/g) and Brand A had the lowest fungal count (0.3 x 10²cfu/g). The AS contamination in commercial diets range from 6% to 30% with an average of 21.2% but the AS contamination in feed ingredients range from 12% to 30% with a mean value of 20.6%. The main AS identified from the commercial diets were Aspergillus terreus (30.3%) and followed by Aspergillus flavus (27.3%) respectively. Among single feed ingredients, the main AS identified was Aspergillus terreus (29.4%),and followed by Aspergillus flavus (23.4%). The results suggested that almost all feeds in this study have some level of AS contamination and this is of concern because of the health hazards it presents to the broilers. The feeds should be periodically examined for ensuring safety towards the poultry optimal performance.